Human resource planning strategy in business organisations (Journal of the College of Basic Education, 2022)
In a rapidly changing world in which information and knowledge flow at an astounding rate and accompanied by material manifestations represented by technology, the need arises with the same speed of flow to know how to manage, develop, plan and develop human resources. And according to the foregoing, the departments will face a constant challenge, which is keeping pace with all new developments in the human resources system in terms of management, development, planning, development and financial systems for this system. Where the international environment shows rapid and dramatic developments, whether in its variables or the requirements of dealing with the trends and needs it has produced.